Binding kinetics of ecotropic (Moloney) murine leukemia retrovirus with NIH 3T3 cells. - Yu, H (1995)
A quantitative analysis of the binding kinetics of intact Moloney murine leukemia retrovirus (MoMuLV) particles with NIH 3T3 cells was performed with an immunofluorescence flow cytometry assay. The virus-cell binding equilibrium dissociation constant (KD), expressed in terms of virus particle concentration, was measured to be 8.5 (+/- 6.4) x 10(-12) M at 4 degrees C and was three- to sixfold lower at temperatures above 15 degrees C. The KD of virus binding is about 1,000-fold lower than the KD of purified MoMuLV envelope. The association rate constant was determined to be 2.5 (+/- 0.9) x 10(9) M-1 min-1 at 4 degrees C and was 5- to 10-fold higher at temperatures above 15 degrees C. The apparent dissociation rate constant at 4 degrees C was 1.1 (+/- 0.4) x 10(-3) min-1 and was doubled for every 10 degrees C increase in temperature over the range tested (15 to 37 degrees C).